Smart Homes and Health Telematics 12th International Conference, ICOST 2014, Denver, CO, USA, June 25-27, 2014, Revised Papers - Bodine, C (Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 12th International Conference on Smart Homes and Health Telematics, ICOST 2014, held in Denver, CO, USA in June 2014. The 21 revised full papers presented together with three keynote papers and 9 short papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on Design and Usability, assistive and sentient environments, cognitive technology, activity recognition, context and situation awareness, Health IT and short contributions.